FRANCISCANISM AND FAMILIES FACTIONS. THE FRANCISCAN ORDER AND ITS PEACEKEEPING ROLE: THE FACTIONS OF CIEZA (1685-1705) - Marín Cano, Alfredo (Revista de Historia Social y de las Mentalidades, 2017)
This article place in the study of the History of the Family trough the analysis of a local elite in the south of Castile, specifically in the murciana town of Cieza during the 17st century. The research explain the configuration and the pattern of these families trough of the material inheritance, immaterial and relational in the context of the disputes of factions, whose goals, articulations and characteristics define the factions of clienteles lineages. Finally in the search of the peace will intervene the own ciezana community, several renowned-man, the Spanish authorities and the parish clergy, particularly the Franciscan order.